SNOW SURFACE FEATURES ALONG THE TRAVERSE ROUTE FROM THE COAST TO DOME FUJI STATION, QUEEN MAUD LAND, ANTARCTICA - フルカワ, テルオ; カミヤマ, コキチ; マエノ, ヒデオ; FURUKAWA, Teruo; KAMIYAMA, Kokichi; MAENO, Hideo (National Institute of Polar Research, 1996)
P(論文) Frequencies of snow surface features such as sastrugi, dunes and thermal cracks were measured along the traverse route from the coastal region to the summit of the Queen Maud Land ice sheet, Dome Fuji Station, East Antarctica. The study route can be clearly divided into three regions on the basis of the regional characteristics of snow surface features : coastal region, katabatic wind region and inland plateau region. The coastal region is characterized by high frequency of small sastrugi and low frequency of dunes. The katabatic wind region is characterized by the co-exis-tence of small and large sastrugi, dunes and glazed surface. The inland region is characterized by low frequencies of small sastrugi and dunes. These regional characteristics of snow surface features reflect the deposition-erosion process affected by surface topography of the ice sheet. Especially, a glazed surface zone where snow accumulation is small develops on relatively steep slopes above the relatively large convex bedrock topography. This indicates that bedrock topography is one of the factors controlling snow accumulation patterns in the katabatic wind region on the Antarctic ice sheet. departmental bulletin paper